2013
DOI: 10.1111/j.1365-2133.2012.11213.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting sunscreen use and sun avoidance in a U.S. national sample of organ transplant recipients

Abstract: Background Organ transplant recipients have an increased risk of non-melanoma skin cancers (NMSC) due to immunosuppressive therapy following transplantation. Use of sunscreen has been shown to reduce this risk. Objectives This study sought to identify patient and healthcare factors associated with sun protective behaviours in organ transplant recipients after transplantation with the goal of increasing overall sunscreen use. Methods This study utilized a cross-sectional, retrospective survey from a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…Occupational, recreational, and holiday sun exposure before and after transplantation and sun protection methods used before and after transplantation were evaluated. The structure of the questionnaire was mainly based on questionnaires published by Moloney et al, Terhorst et al, and Mihalis et al and then modified and adapted to the local language and circumstances. All OTRs who were willing to participate in the study were included if at least one summer had elapsed since their transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…Occupational, recreational, and holiday sun exposure before and after transplantation and sun protection methods used before and after transplantation were evaluated. The structure of the questionnaire was mainly based on questionnaires published by Moloney et al, Terhorst et al, and Mihalis et al and then modified and adapted to the local language and circumstances. All OTRs who were willing to participate in the study were included if at least one summer had elapsed since their transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…Prior UV photography research has controlled for self-reported skin sensitivity (6, 7), and other studies have linked skin type to sun protection behaviors (28, 29). …”
Section: Methodsmentioning
confidence: 99%
“…It has been well documented that OTR have insufficient knowledge about the consequences of sun exposure, as well as inadequate sun‐protective behaviour, highlighting the need for more effective educational interventions. Factors that affect sun‐protective behaviour have been identified in OTR, and several educational interventions have been evaluated for short‐term efficacy (≤ 2 years). Successful strategies that have promoted sun‐protective habits in OTR include counselling from dermatologists, written information pamphlets, word books with and without repetitive text/e‐mail reminders tailored to weather conditions and mobile medical applications .…”
Section: Modifying Sun‐protection Behaviour In Organ Transplant Recipmentioning
confidence: 99%